Murray, S. (2020). Disability and the posthuman: Bodies, technology, and cultural futures. Liverpool University Press - Yayalar, Emine Öncüler (Journal of Posthumanism, 2024)
In Disability and the Posthuman: Bodies, Technology, and Cultural Futures (2020), Stuart F. Murray presents an insightful exploration of the intersections of posthumanism and disability studies and offers a compelling framework for understanding how these disciplines can mutually inform and enrich one another. Embedded firmly within critical disability studies, Murray explores the productive potentials of an encounter between posthumanism and disability studies. His analysis mainly focuses on the disruptive nature of disability and its implications for envisaging a posthumanist future. While integrating posthumanism with disability studies is not unprecedented, Murray distinguishes his work through a unique emphasis on cultural representations, contributing a fresh perspective to the literature.